2019
DOI: 10.1253/circj.cj-18-0543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics and 3-Year Outcomes in Patients With Acute Heart Failure With Preserved, Mid-Range, and Reduced Ejection Fraction

Abstract: and dramatic improvement in long-term outcomes of chronic HF, 4 patients with AHF continue to experience unacceptably high short-term mortality and re-hospitalization rates, which have not improved markedly over the past decades. 5 HF is most commonly classified according to the severity H eart failure (HF) is a major public health problem affecting an estimated >23 million patients globally. 1 It remains the leading cause of hospitalization among adults >65 years of age, 1 and imposes a substantial socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
43
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 29 publications
11
43
0
5
Order By: Relevance
“…Third, our study is also first in the literature analysing very elderly patients with HFmrEF. Previous studies have shown that patients with HFmrEF had clinical characteristics intermediate between those in the HFrEF and HFpEF groups . The similar characteristics to those with HFpEF include older age, female sex, comorbidities (hypertension, chronic obstructive pulmonary disease, diabetes mellitus and laboratory values ‐BNP and troponin‐) and medication use (beta‐blockers, ACE‐Is and ARBs) .…”
Section: Discussionmentioning
confidence: 97%
“…Third, our study is also first in the literature analysing very elderly patients with HFmrEF. Previous studies have shown that patients with HFmrEF had clinical characteristics intermediate between those in the HFrEF and HFpEF groups . The similar characteristics to those with HFpEF include older age, female sex, comorbidities (hypertension, chronic obstructive pulmonary disease, diabetes mellitus and laboratory values ‐BNP and troponin‐) and medication use (beta‐blockers, ACE‐Is and ARBs) .…”
Section: Discussionmentioning
confidence: 97%
“…17,19 On the other hand, a meta-analysis demonstrated that HFmrEF had a lower rate of cardiac mortality than HFrEF. 20 This discrepancy might be due to the difference in patient characteristics and treatment in each cohort.…”
Section: Discussionmentioning
confidence: 99%
“…22 In an acute heart failure study, Cho et al found higher in-hospital mortality and lower long-term survival rates in the rEF than mrEF and pEF groups with non-ischemic etiology. 21 Fonarow et al reported a higher prevalence of heart failure with pEF and similar mortality and rehospitalization rates regardless of LVEF category after discharge. 23 Various conclusions were made regarding the prognosis in heart failure patients in terms of LVEF differences; nevertheless, there was no definite confirmation.…”
Section: Disclosuresmentioning
confidence: 93%